(untitled) (Italian Journal of Public Health, 2012)
Background: young persons are most strongly affected by displacement through political/military actions. This is also a European problem as well as an issue for the European Union. Applying the social-ecological model by Bronfenbrenner we concentrated on micro- and mesosystems of Austrian adolescents and migrant adolescents of war-affected countries. Methods: a questionnaire was administered to adolescents in Austria attending schools beyond the mandatory school age, yielding a sample of about 1 100 students from Austrian and immigrant background. We used analysis of variance to compare host and immigrant youth as well as regression analysis to assess the impact of risk and protective factors on youth outcomes. Results: we do find sex differences for protective factors and youth outcomes but few differences between immigrant and Austrian adolescents. Youth outcomes analysed were somatic symptoms, anxiety, depression, self-esteem, anti-social behaviour, substance use, and academic performance. Important risk factors turned out to be intergenerational conflict, exposure to violence, and social distance. Protective factors include family connectedness, parental monitoring, school connectedness, peer support, and neighbourhood attachment. Conclusions: the most important protective factor is school connectsdness. Social distance and intergenerational conflict are the dominant risk factors influencing youth outcomes. Our research leads to a better understanding of factors determining the well-being of adolescents and contributes to finding new approaches to prevent or cope with mental health problems of young immigrants. In particular it appears to be important to keep young persons in education and/or training since school connectedness influences mental health and well-being positively.